(untitled) (Scientific journal of the Fergana State University, 2025)
This research dedicated to the age-specific norms of physical activity of school students focuses on studying the unique characteristics of physical development and motor skills of children and adolescents of different ages. The main indicators of physical activity (speed, strength, endurance, flexibility, balance, and coordination) are analyzed across various age groups, and their age-related changes are identified. The results obtained serve as a basis for developing practical recommendations for physical education classes for school students, as well as for promoting a healthy lifestyle. The research aims to strengthen the physical health of school students and improve their motor activity.